PROPERTIES OF THE DEMONSTRATION OF THE ECOLOGICAL OUTLOOK OF A PERSON IN A PERIOD WHEN GLOBAL ENVIRONMENTAL PROBLEMS ARE ESCALATING - G'affarova Gulchehra G'ulamjanovna,; Kandov Bahodir Mirzaevich,; Togaev Shavkat Khurramovich, (The Bioscan, 2024)
This article explores the trend of globalization of environmental relations, requiring radical qualitative changes not only in lifestyle, worldview, environmental knowledge, legal culture, but also in the worldview of people in a particular country or region. In addition, the time to resolve these problems is very short. At the same time, the global human impact on the environment is very strong. To solve the problem, which is extremely important all over the world, people with high intelligence, intellectual potential and huge economic resources, technical and technological base are required.